A new mouse model of ankle instability induced by multiple mechanical sprains with controlled inversion angle and speed - Ching, Shih-Hong; Chiu, Yen-Chun; Liao, Yu-Ching; Yang, Shang-Hsun; Tsai, Yi-Ju (Frontiers in Bioengineering and Biotechnology, 2022)
Ankle sprain occurs by a sudden and extreme inversion and plantarflexion at the ankle joint to cause the ligamentous injuries. A portion of ankle sprain patients experiences recurrent ankle sprains and develops chronic ankle instability (CAI). The present CAI animal models are a single event with severe ligamentous injury using surgical transection of ligaments or manually overextending the ankle. Purpose: To simulate the mechanical and recurrent sprain injuries in CAI patients, we establish a new ankle instability model with multiple ankle injuries using a self-designed machine to sprain the ankle with a controlled inversion angle and speed. Methods: Male C57BL/6J mice were used and respectively subjected to sham operation, calcaneofibular ligament (CFL) transection and mechanical ankle sprains. Three mechanical sprains were performed at the 13th and 185th day after the initial mechanical ankle sprain. Results: The first mechanical sprain and CFL transection induced ankle injury as indicated by an average of 62% decrease in ankle pressure pain threshold and 114% increase in ankle thickness compared with the contralateral untreated ankle. The second and third mechanical sprain induced recurrent ankle injuries. The foot slips in beam tests were increased after mechanical ankle sprains but not after CFL transection indicating the induction of motor balance deficits. Multiple mechanical ankle sprains induced significant gait changes in longer duration of stance (an average of 194% increase), swing (134%), and step cycle (147%) compared with CFL transection or sham operation, and slowly walking speed (78% reduction) and shorter step distance (91%) after the third sprain. Conclusion: These results elucidate that multiple mechanical sprains induce recurrent ankle injuries, balance defects, and gait changes to be a good model for investigating the mechanisms of CAI induced by recurrent sprain injuries.